Detection and Phylogenetic Analysis of Porcine Deltacoronavirus in Korean Swine Farms, 2015. Issue 3 (10th March 2016) - Lee, J. H.; Chung, H. C.; Nguyen, V. G.; Moon, H. J.; Kim, H. K.; Park, S. J.; Lee, C. H.; Lee, G. E.; Park, B. K.
Summary: This study applied molecular‐based method to investigate the presence of porcine deltacoronavirus (PDCoV) in 59 commercial pig farms in South Korea. The results of RT‐PCR screening on a relatively large collection of faeces samples ( n  = 681) from January 2013 to March 2015 did not reveal the presence of PDCoV until the end of 2014. However, on March 2015, PDCoV‐positive samples (SL2, SL5) were detected from SL swine farm in Gyeongbuk province. The phylogenetic trees based on the complete spike‐ and nucleocapsid protein‐coding genes showed that SL2 and SL5 closely related to the US PDCoV strains rather than those in China. Thought Korean strains of PDCoV isolated in 2014 (KNU14.04) and in 2015 (SL2 and SL5) grouped within US PDCoV cluster, the reconstruction of ancestral amino acid changes suggested that they are different.